PERLINDUNGAN HUKUM TERHADAP MAHASISWA MAGANG MERDEMA BELAJAR KAMPUS MERDEKA DITINJAU DARI HUKUM KETENAGAKERJAAN - Nassa Dwiyanti Mokodongan (Jurnal Perspektif Hukum, 2026)
The Independent Learning-Independent Campus (MBKM) program aims to connect higher education with the world of work, one of which is through internships. However, student interns often face problems, such as exploitation of working hours, lack of compensation, and the absence of social security protection. This study aims to analyze legal protection for MBKM student interns from a labor law perspective. Using a normative juridical approach, this study examines regulations such as Law Number 13 of 2003 concerning Manpower, Minister of Manpower Regulation Number 6 of 2020, and other related regulations. The results show that student interns have the right to legal protection, including guarantees of occupational safety, adequate compensation, and humane treatment. However, in practice, violations such as unpaid overtime and failure to register with the Social Security Agency (BPJS Ketenagakerjaan). Furthermore, the lack of clarity regarding the legal status of student interns exacerbates the situation, making them vulnerable to exploitation. The government has a constitutional responsibility to ensure this protection is in accordance with Articles 27 and 28 of the 1945 Constitution. This study recommends harmonization of the National Education System Law and the Manpower Law, as well as strengthening oversight mechanisms to protect the rights of student interns. Educating students about their rights is also crucial to prevent violations. With adequate protection, the MBKM program can operate in accordance with the principles of social justice and support the goal of producing competent, work-ready graduates.